Demand Ischemia as a Predictor of Mortality in Older Patients With Delirium - Kumar, Manish; Patil, Shivaraj; Godoy, Lucas Da Cunha; Kuo, Chia-Ling; Swede, Helen; Kuchel, George A.; Chen, Kai (Frontiers in Cardiovascular Medicine, 2022)
Introduction: The impact of demand ischemia on clinical outcomes in patients with delirium remains largely unexplored. This study aims to evaluate the effects of demand ischemia in older patients with delirium on in-hospital mortality and length of stay (LOS) using the largest US inpatient care database, National Inpatient Sample (NIS). Methods: We obtained data from the year 2010-2014 National Inpatient Sample (NIS). We used the International Classification of Diseases-Ninth Edition-Clinical Modification (ICD-9-CM) diagnosis codes to identify all the records with a primary or secondary diagnosis of delirium with or without demand ischemia and other clinical characteristics. We then compared in-hospital mortality and length of stay (LOS) in patients with and without demand ischemia. Results: We analyzed 232,137 records. Patients with demand ischemia had higher overall in-hospital mortality than those without demand ischemia (28% vs 12%, p<0.001). After adjusting for clinical comorbidities and complications, demand ischemia was no longer associated with increased in-hospital mortality (OR: 1.14; 95% CI: 0.96-1.35; p = 0.141). However, further analysis with the exclusion of critically ill patients with non-cardiogenic shock or mechanical ventilation showed a significant association of demand ischemia with increased in-hospital mortality (adjusted OR: 1.39; 95% CI: 1.13-1.71; p = 0.002). Among non-critically ill survivors, patients with demand ischemia had a longer median LOS [4, (3-7) days] than those without demand ischemia [4, (2- 6) days] (p<0.001). However, the difference was not statistically significant after adjustment for covariates. Conclusion/Relevance: Demand ischemia did not affect mortality in critically sick patients. In non-critically ill patients, however, demand ischemia was significantly associated with increased in-hospital mortality, likely due to the severity of the underlying acute illness. Measures aimed at mitigating risk factors that contribute to delirium and/or demand ischemia need to be explored.